The Intertwined World of the Oral and Written Transmission of Sacred Traditions in the Middle East - Alba Fedeli; Geoffrey Khan; Johan Lundberg (Open Book Publishers, 2025)
In the medieval Middle East, the scriptures of Christianity, Judaism and Islam were transmitted in written and oral form. The means of written transmission and the textualisation of the oral reading of these scriptures exhibit many parallels, which reflect cultural contact and convergence across the various religious communities. This volume is the outcome of a project, funded jointly by the Deutsche Forschungsgemeinschaft and the Arts and Humanities Research Council, that aimed to bring together strands of research related to various aspects of the transmission of these sacred texts in order to reach a deeper understanding of the intertwined world of the three major religions of the Middle East at their formative periods of development during the early Islamic centuries.